The Secularization of Christianity in Postmodernity. Challenges and opportunities in a new context - Porcel Moreno, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This paper intends to show how the nihilism that underlies the different ways in which postmodern secularization presents not only leads to the denuclearization of the religious precisely by emptying its specific contents, but also relegates all religious experience to the private sphere of the individual conscience. This nihilistic context of postmodernity would impose the time of religion without religion, which consists of living apparently as if we were religious subjects when, in reality, we are not. Undoubtedly, this new postmodern horizon poses a challenge for Christianity. For this reason, we will try to indicate the three major challenges that Christianity must face, so that the nihilistic logic of postmodern secularization does not end up infecting the logic of the religious as well, and to glimpse what promising opportunities are presented to Christianity today, to think about its own essence and to show its praxis founded on charity in this time in which we live.